Exploration of P-Mentan-3-OL Compounds Through Catalytic Reaction Against Sitronelal Using Cu / ZnBr2 / γAl2O3 Catalyst and Gas N2 and H2 - Ajeng Santiara; Cicilia Shinta Putri Cahyani; Elvina Dhiaul Iftitah (Natural B, Journal of Health and Environmental Sciences, 2014)
Exploration compound p-menthan-3-ol has been carried out using Cu/ZnBr2/γ-Al2O3 as a catalyst in N2 and H2 atmospheric gases. This research was done in several stages that is Cu/ZnBr2/γ-Al2O3 catalyst preparation, catalyst characterization, and catalytic reactions toward citronellal. Impregnation of Cu (NO3)2.3H2O in ZnBr2/γ-Al2O3 wasperformed in methanol as a solvent for Cu/ZnBr2/γ-Al2O3 catalyst preparation. Stage was followed by a catalytic reaction to citronellal that performed in a glass reactor modification with atmospheric gases H2; N2 and H2 at 90 OC temperature variations and 120 OC. Catalyst characterizations was performed using XRD and SEM - EDX, so it could be seen with either Cu was impregnated on ZnBr2/γ-Al2O3. Gas chromatography (GC) and gas chromatography - mass spectrum (GC-MS) was used to determine the activity of the catalyst through a catalytic reaction product analysis. Isopulegol was obtained from the product p- menthan-3-ol with a selectivity of 37.75 % in H2 gas atmosphere at a temperature of 120 OC for 4 hours, and isopulegol selectivity was obtained in atmospheric gases N2: H2 = 3:2 at a temperature of 120 OC with reaction time of 4 hours was equal to 25.82 % .